Mechanisms of retinal ganglion cell injury following acute increases in intraocular pressure - Garner, Mary Anne; Strickland, Ryan G.; Girkin, Christopher A.; Gross, Alecia K. (Frontiers in Ophthalmology, 2022)
The maintenance of intraocular pressure (IOP) is critical to preserving the pristine optics required for vision. Disturbances in IOP can directly impact the optic nerve and retina, and inner retinal injury can occur following acute and chronic IOP elevation. There are a variety of animal models that have been developed to study the effects of acute and chronic elevation of IOP on the retina, retinal ganglion cell (RGC) morphology, intracellular signaling, gene expression changes, and survival. Acute IOP models induce injury that allows for the study of RGC response to well characterized injury and potential recovery. This review will focus on the initial impact of acute IOP elevation on RGC injury and recovery as these early responses may be the best targets for potential therapeutic interventions to promote RGC survival in glaucoma.